Studies in the genus Hypericum L. (Hypericaceae) 5(1). Sections 10. Olympia to 15/16. Crossophyllum - Robson, Norman K. B. (Phytotaxa, 2013)
Part 5(1) of this monographic series of papers on the genus Hypericum contains treatments of Section 10. Olympia and its relatives (Sections 11. Campylopus–16. Crossophyllum), which form a Euro-Mediterranean group centred in south-western Turkey and extending in area from the Caucasus to Macaronesia, north to Scotland, Denmark and southern Sweden, east to Belarus and the Ukraine and south to north-west Africa and Israel. Section 15. Thasia has been included in Section 16. Crossophyllum. Two new species are described in Section 12. Origanifolium (H. laxiflorum N.Robson, sp. nov. and H. ichelense N.Robson, sp. nov.) and five changes of rank are made; in Section 10. Olympia: H. lycium(N.Robson & Hub.-Mor.) N.Robson, stat. nov. and H. auriculatum (N.Robson & Hub.-Mor.) N.Robson, stat. et nom. nov.; in Section 12. Origanifolia: H. origanifolium var. depilatum (Freyn & Bornm.) N.Robson, stat. nov., H. bourgaei (Boiss.) N.Robson, stat. nov. and H. albiflorum (Hub.-Mor.) N.Robson, stat. nov. In addition, in Section 14. Oligostema, Druce’s name for the hybrid H. linariifolium × humifusum has been validated (H. × caesariense Druce ex N.Robson, hybr. nov.); and H. leprosiforme O.Schwartz has been moved from Section 12. Origanifolia to Section 27.Adenosepalum.